For this case we have the following function:
![f (x) = - x ^ 2 + 13x-36](https://tex.z-dn.net/?f=f%20%28x%29%20%3D%20-%20x%20%5E%202%20%2B%2013x-36)
To find the zeros of the function we make
and solve for "x", then:
![0 = -x ^ 2 + 13x-36](https://tex.z-dn.net/?f=0%20%3D%20-x%20%5E%202%20%2B%2013x-36)
We multiply by -1 on both sides of the equation:
![0 = x ^ 2-13x + 36](https://tex.z-dn.net/?f=0%20%3D%20x%20%5E%202-13x%20%2B%2036)
We factor the equation, for this we look for two numbers that, when multiplied, result in 36 and when added, result in -13. These numbers are -9 and -4.
![(-9) * (- 4) = 36\\-9-4 = -13](https://tex.z-dn.net/?f=%28-9%29%20%2A%20%28-%204%29%20%3D%2036%5C%5C-9-4%20%3D%20-13)
Thus, the factored equation is:
![(x-9) (x-4) = 0](https://tex.z-dn.net/?f=%28x-9%29%20%28x-4%29%20%3D%200)
Therefore, the roots are:
![x_ {1} = 9\\x_ {2} = 4](https://tex.z-dn.net/?f=x_%20%7B1%7D%20%3D%209%5C%5Cx_%20%7B2%7D%20%3D%204)
Answer:
![x_ {1} = 9\\x_ {2} = 4](https://tex.z-dn.net/?f=x_%20%7B1%7D%20%3D%209%5C%5Cx_%20%7B2%7D%20%3D%204)